2019
DOI: 10.1080/19336950.2019.1600967
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of periodic paralysis and paramyotonia congenita caused by SCN4A gene mutations two family reports and literature review

Abstract: Objective : To verify the diagnosis of channelopathies in two families and explore the mechanism of the overlap between periodic paralysis (PP) and paramyotonia congenita (PMC). Methods : We have studied two cases with overlapping symptoms of episodic weakness and stiffness in our clinical center using a series of assessment including detailed medical history, careful physical examination, laboratory analyses, muscle biopsy, electrophysiological evaluation, and genetic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…Patients described as having "no persistent/fixed weakness" or "no weakness," or "no abnormal findings in neurological examination" were considered "no persistent weakness" cases. In the 55 papers analyzed (more than 76 pedigrees, 267 cases; [6,10,14], and 23 had no description regarding weakness distribution [7,9]. Among 51 patients carrying the SCN4A T1313M mutation described in the 13 studies (more than 14 pedigrees; Table 3), 5/51 had persistent weakness [6,10,13], 17/50 had no weakness, and 29/51 had no description about weakness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients described as having "no persistent/fixed weakness" or "no weakness," or "no abnormal findings in neurological examination" were considered "no persistent weakness" cases. In the 55 papers analyzed (more than 76 pedigrees, 267 cases; [6,10,14], and 23 had no description regarding weakness distribution [7,9]. Among 51 patients carrying the SCN4A T1313M mutation described in the 13 studies (more than 14 pedigrees; Table 3), 5/51 had persistent weakness [6,10,13], 17/50 had no weakness, and 29/51 had no description about weakness.…”
Section: Discussionmentioning
confidence: 99%
“…While persistent muscle weakness in PC patients is rare [2], a small number of case reports have reported patients who presented with mild weakness (mainly proximal dominant) [3][4][5][6][7][8][9][10][11][12][13][14]. Here, we present the detailed phenotype of a Japanese family with a history of PC accompanied by severe distal weakness together with masticatory muscle involvement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…T704M mutation in the S5 segment of domain II can result in impaired fast or slow inactivation of Na V 1.4 channel, and, therefore, persistent increased sodium current and sarcolemmal depolarization, which can result in the symptom of paralysis [32,33]. It has been reported that T704M mutation can cause NormoPP [7,10].…”
Section: Geneticsmentioning
confidence: 99%